Unlocking the history of a trans‐Atlantic invader: did the human slave trade impact Brown mussel dispersal? - Calazans, Sávio H. (2021)
Aim Brown mussels exhibit a trans-Atlantic distribution putatively caused by either native dispersal or artificial gene flow, likely in concert with the transport of enslaved people from Africa. Evolutionary history and demographic models of this widespread species may clarify how the present-day distribution was impacted by natural versus artificial dispersal. Particularly, dating the timing of the South American/African split may determine whether the human slave trade likely impacted the contemporary distribution of brown mussels. Location Coastal Brazil, Morocco, South Africa, and Mozambique. Taxon Perna perna (Linnaeus 1758). Methods We genotyped a total of 644 samples from 18 populations at 10 microsatellite loci. We estimated genetic structure with clustering algorithms in STRUCTURE and GENETIX. We estimated genetic distances by characterizing patterns of pair-wise F-ST using the program FSTAT, evaluating differences among and between regions via AMOVA, and testing isolation by distance in IBDWS. To estimate and date the most likely pathway by which P. perna crossed the Atlantic Ocean we used Bayesian factors from thermodynamically heated coalescent simulations in the program MIGRATE-n. Results We found no general pattern of reduced or elevated levels of genetic diversity within any region across site or locus. We identified four genetic clusters: East South Africa (ESA), West South Africa (WSA), Brazil (BR) and North Africa (MO); F-ST ranged from 0.06 to 0.11 among regions and exhibited a significant pattern of isolation by distance. Migration models indicated that P. perna dispersed from WSA to MO and from there to BR of approximately 2,000 years. Main conclusions Multiple lines of evidence suggest the Brazilian populations of P. perna have been a long-standing native population, originating from northern Africa and are unlikely a consequence of the African slave trade. Although, human introduction cannot be ruled out South American P. perna populations exhibited genetic characteristics indicative of a divergent, isolated and established population, featuring the genetic signature expected for a native population.